1985
DOI: 10.1002/ar.1092130414
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of human cardiac outflow

Abstract: The developmental anatomy of human cardiac outflow was studied in a series of 16 normal embryos (gestational days 29-39, crown-rump length 6-20 mm, stages 14-19). Structural features and kinetics during truncal septation (TS) were described from external photographs, serial histological sections, and computer graphic reconstructions of selected tissues. Early in the period studied, the tubular myocardium ensheathed the single cardiac lumen and spiralling conotruncal ridges, which were filled with mesenchymal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 18 publications
5
39
0
Order By: Relevance
“…They have a so-called bulbus arteriosus, which is not enclosed by cardiac muscle, but by elastic tissue and smooth muscle, and therefore is considered to be a specialization of the proximal part of the ventral aorta (256). However, similar to the mammalian condition (306,326,339), the bulbus arteriosus in zebrafish embryonic hearts is surrounded by myocardium that disappears with development (134,135). The bony fish bulbus arteriosus might thus be homologous to the shark conus arteriosus and amphibian/mammalian bulbus cordis.…”
Section: Fishesmentioning
confidence: 94%
See 1 more Smart Citation
“…They have a so-called bulbus arteriosus, which is not enclosed by cardiac muscle, but by elastic tissue and smooth muscle, and therefore is considered to be a specialization of the proximal part of the ventral aorta (256). However, similar to the mammalian condition (306,326,339), the bulbus arteriosus in zebrafish embryonic hearts is surrounded by myocardium that disappears with development (134,135). The bony fish bulbus arteriosus might thus be homologous to the shark conus arteriosus and amphibian/mammalian bulbus cordis.…”
Section: Fishesmentioning
confidence: 94%
“…Finally, two components, which we have called "evolutionarily conserved" elements, are now incorporated into the chambers, namely, the atrioventricular canal into the atrial chambers (171,172,331) and the proximal part of the outflow tract into the ventricular chambers; the distal part loses its myocardium to the semilunar valves (306,326,339). The myocardium of the atrioventricular canal has retained some of its primary features (196), but the outflow tract has retained hardly any primary feature (208).…”
Section: The Atrial and Ventricular Chambersmentioning
confidence: 99%
“…Early understanding of the morphological and fusion events in the developing heart came from histological and SEM studies. Moreover, direct comparisons of this morphogenetic process have been made between mouse, chicken and human embryonic hearts (Pexieder, 1978;Thompson et al, 1985;Vuillemin and Pexieder, 1989). Unfortunately, the advances in in vitro organ culture methods that spurred a mechanistic understanding of palate and neural tube fusion have lagged behind in the field of heart development.…”
Section: Tissue Fusion In the Developing Heart Heart Morphogenesismentioning
confidence: 99%
“…In spite of classical detailed descriptions of early development of the arterial pole of the human heart (e.g., [8,9,10]), we had no or few information about changes in topographical relation between the DA and left subclavian artery. In the present study, we found 5 specimens including the final approach of DA (within 1-vertebral segment) to the left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%